Pengembangan Perangkat Lunak Pembelajaran Penulisan Aksara Bali Menggunakan SDLC Untuk Anak-Anak (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Balinese script is a traditional script originating from Bali. To maintain sustainability, formal education in schools through Balinese language subjects is one if many ways to maintain it. Apart from studying at school, it would be even better if Balinese script learning could be done outside of school by appealing to the concept of learning. One way to create interesting learning is through application games. Making a Balinese script writing application aims to help students learn Balinese script by implementing the Software Development Life Cycle (SDLC) and Black Box testing of making Balinese script writing applications. Making the application is expected to be one of the media that can assist students in learning Balinese script.